2017
DOI: 10.1002/jmv.24941
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of microRNA profiles by a novel inhibitor of human La protein in HBV‐transformed human hepatoma cells

Abstract: A pyrazolopyridine HBSC11 was previously identified as a novel inhibitor of human La protein with anti‐hepatitis B virus (HBV) activity. However, the underlying mechanism(s) of HBV inhibition by HBSC11 remains unclear. This study aimed to examine the regulation of microRNA (miRNA) by HBSC11 in HBV‐transformed human hepatoma HepG2.2.15 cells using microarray and quantitative real‐time PCR. Target genes of the differentially expressed miRNAs were predicted and subjected to bioinformatics analysis. Results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Recently, we used microarray and quantitative real‐time PCR to investigate the mechanism of H11‐mediated inhibition of HBV infection. The results showed that HBSC11‐induced inhibition of HBV replication was mediated via miR‐ 3912‐5p, miR‐6793‐5p, and miR‐7159‐5p and participation in the Wnt, beta‐catenin, and PPAR signaling pathways . Further research is underway on this subject.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, we used microarray and quantitative real‐time PCR to investigate the mechanism of H11‐mediated inhibition of HBV infection. The results showed that HBSC11‐induced inhibition of HBV replication was mediated via miR‐ 3912‐5p, miR‐6793‐5p, and miR‐7159‐5p and participation in the Wnt, beta‐catenin, and PPAR signaling pathways . Further research is underway on this subject.…”
Section: Discussionmentioning
confidence: 94%
“…La protein functions as an RNA chaperone and advances the synthesis of tRNA by processing the pre-tRNA precursor's 5-and 3-prime terminals. La protein interacts with particular RNA molecule types to control how they are processed downstream, stop them from misfolding, and promote proper transcript folding and maturation [25,26]. La protein also participates in the mRNAs' internal ribosome entry site (IRES)-mediated translation pathway [27].…”
Section: Introductionmentioning
confidence: 99%
“…It combines with specific RNA molecules to regulate its downstream processing. La protein promotes the correct folding of transcripts, prevents the misfolding, and promotes the maturation of transcripts ( 6 , 7 ). It also participates in the internal ribosome entry site (IRES)-mediated translation of mRNA ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%